2001
DOI: 10.1200/jco.2001.19.17.3766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Dose Chemotherapy on Peripheral T-Cell Lymphomas

Abstract: Our results are comparable to the published data on HDCT in B-cell non-Hodgkin's lymphoma (NHL) patients despite the fact that patients with PTCL are known to have a worse outcome compared with B-cell NHL patients. Considering the dismal outcome of conventional chemotherapy in PTCL patients, these data suggest the hypothesis that the poor prognostic implication of T-cell phenotyping in NHL might be overcome by frontline HDCT and transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 20 publications
6
94
0
Order By: Relevance
“…However, the numbers of patients in the various studies are relatively small. [6][7][8] These results are similar to a comparable group of patients with B-cell lymphomas. 7,9 The role of allogeneic stem cell transplantation (Allo-SCT) for the treatment of relapsed lymphoma remains unclear, although it has been demonstrated to be an effective salvage strategy in selected patients.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the numbers of patients in the various studies are relatively small. [6][7][8] These results are similar to a comparable group of patients with B-cell lymphomas. 7,9 The role of allogeneic stem cell transplantation (Allo-SCT) for the treatment of relapsed lymphoma remains unclear, although it has been demonstrated to be an effective salvage strategy in selected patients.…”
Section: Introductionsupporting
confidence: 77%
“…[2][3][4][5] Patients with PTCL treated with conventionaldose chemotherapy alone, demonstrated a 5-year survival of 38% (95% confidence interval (CI), 35-54%) compared to patients with B-cell disease who demonstrated a 5-year survival of 63% (95% CI 53-73%, P ¼ 0.001), a difference that was maintained when stratified using the IPI and MD Anderson tumour score. 4,6 Cumulative experience has shown that high-dose chemotherapy is an effective salvage therapy in B-cell malignant lymphoma. 5 However, data examining the impact of high-dose chemotherapy with autologous haemopoietic stem cell rescue in PTCL are limited.…”
Section: Introductionmentioning
confidence: 99%
“…15,35,36 Similarly, Corradini et al 35 reported 17 patients with relapsed or refractory disease who underwent a reduced intensity allogeneic procedure. The authors found an impressive OS of 80% and PFS of 60% at 3 years.…”
Section: Allo-hsct For Ptclmentioning
confidence: 99%
“…5 On the other hand, the outcomes were equivalent in patients treated with high-dose sequential chemotherapy followed by autologous transplantation (ASCT). [25][26][27][28][29][30] It has been reported that there is marked variability in the 5-year relative survival rate across PTCL subtypes, and that there has been no clear improvement in survival among PTCL patients over time. 31 This finding is in sharp contrast to the improvement in OS seen for B-cell NHLs over the same time period, [18][19][20][21] which is due mainly to advances in therapy, particularly the addition of immunotherapy using anti-CD20 rituximab.…”
Section: Figmentioning
confidence: 99%